Two new marine species of Cryptosphaeria (Diatrypaceae, Sordariomycetes) from the Red Sea mangroves - Abdel-Wahab, Mohamed A.; Jones, E.b. Gareth; Bahkali, Ali H. (Phytotaxa, 2025)
Two new species of Cryptosphaeria are described and illustrated from decaying intertidal wood of Avicennia marina in the mangroves of the Red Sea, specifically from Egypt and Saudi Arabia. Cryptosphaeria jizanensis sp. nov. was recorded from the mangroves of Farasan Island, Jizan City, Saudi Arabia, while Cryptosphaeria maris-rubri was identified in the mangroves of Safaga, Egypt. Phylogenetic analyses of the combined LSU, SSU, and ITS sequence data placed these two new Cryptosphaeria species within a monophyletic clade alongside C. avicenniae and C. bathurstensis. Cryptosphaeria jizanensis differs from other species in the genus by its well-developed entostroma and entoplacodial stroma. In contrast, C. maris-rubri is unique among its relatives due to the production of pseudoparenchymatous ectostroma and an asexual stage characterized by two types of conidia α and β. A key to marine Cryptosphaeria is provided.